Is There an Association between Maternal Thrombophilia and Oligohydramnios During the Gestational Age of 18-23 Weeks? A Case-Control Study - Basha, Asma (Jordan Medical Journal, 2016)
Objective: To study the prevalence of genetically related thrombophilic Factor V Leiden, Factor V Cambridge, prothrombin gene mutation G20210A, factor XIII, methylenetetrahydrofolate reductase (MTHFR) C677T and A1298C mutations in pregnant women with oligohydramnios at the gestational age of 18-23 weeks. Methods: A case-control study was conducted in Jordan, at Jordan University Hospital and Farah Hospital between 2007 and 2011. Sixty three pregnant women with oligohydramnios were compared with 85 pregnant women with normal amniotic fluid volume at the gestational age of 18-23 weeks. All the fetuses have satisfactory fetal anomaly scan and there was no history suggestive of preterm premature rupture of the membranes. All subjects were investigated for 6 genetically related thrombophilic factors. Results: The presence of MTHFR C677T was found to be significantly higher in the oligohydramnios group compared to the control group, 61.9% vs. 37.6% (p value 0.01), and The presence of heterozygosity for pregnant women with oligohydramnios (49.2%) was also significant (p value 0.005) compared to the control (29.4%). Factor XIII, Factor II G20210A, MTHFR A1298C, Factor V Leiden were not found to have a statistically significant difference between the two groups. Factor V Cambridge was found in none of the cases, but was found in 3% of the control group (p value 0.32). Conclusions: This study suggests that the presence of MTHFR C677T in women with oligohydramnios at the time of fetal morphology scan may indicate a placental mal-function; however, larger studies are needed to validate this association.